2012
DOI: 10.5713/ajas.2012.12339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-diarrhoeal Herbs on Growth Performance, Nutrient Digestibility, and Meat Quality in Pigs

Abstract: Two studies were conducted to investigate the effects of anti-diarrhoeal herbs on growth performance, nutrient digestibility, and meat quality in pigs. In Exp 1, 150 weanling-growing piglets (average BW = 7.5±0.24 kg, average age = 27±1 d) were allotted into one of the five dietary treatments, including: i) CON, basal diet, ii) DP, basal diet+1 g/kg date pits, iii) JH, basal diet+0.5 g/kg Japanese-honeysuckle, iv) HCT, basal diet+1 g/kg houttuynia cordata thunb, and v) LE, basal diet+1 g/kg laquer tree extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…However, in the present experiment, no significant differences on RBC, WBC, Lymphocyte, TNF-a, IL-1b and IL-6 concentrations were detected. In agreement with our results, Cho et al (2012) reported that dietary supplementation with herbs (yellow ginger or hoantchy root) did not affect WBC, RBC or lymphocyte concentrations in growingfinishing pigs. In the present study, the lack of effect on WBC RBC, lymphocyte, TNF-a, IL-1b and IL-6 concentrations could be due to the maturation of pigs' immune system in finishing phase or the low concentrations of herbs used.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the present experiment, no significant differences on RBC, WBC, Lymphocyte, TNF-a, IL-1b and IL-6 concentrations were detected. In agreement with our results, Cho et al (2012) reported that dietary supplementation with herbs (yellow ginger or hoantchy root) did not affect WBC, RBC or lymphocyte concentrations in growingfinishing pigs. In the present study, the lack of effect on WBC RBC, lymphocyte, TNF-a, IL-1b and IL-6 concentrations could be due to the maturation of pigs' immune system in finishing phase or the low concentrations of herbs used.…”
Section: Discussionsupporting
confidence: 93%
“…Ra et al (2003) reported that the plant extracts-administered group showed higher (49.3% and 52.3%) growth promotion than the control group (46.2%), by the increase in the GH and IGF-1 levels in rats. Antidiarrheal herbs can improve growth performance and prevent diarrhea in pigs (Cho et al, 2012). Klindt et al (1998) reported that the injected pigs showed greater BW gain than those on the control treatment, and backfat deposition rate was not influenced by the administration of IGF-1.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, urushiol is an oily organic component and exerts several beneficial effects such as antimicrobial [ 7 ], and antioxidant [ 8 ] activities. Due to the afore-mentioned effects [ 7 , 8 ], RV and urushiol were tested as the feed supplements to enhance health and/or productivity in pigs [ 9 , 10 ] and broiler chickens [ 11 ]. However, it is reported that urushiol might have toxic effects as it is the main antigen of Rhus and exhibits strong antigenicity in animals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%